Faktor Yang Mempengaruhi Tingkat Pengembalian Kredit Pada Program Simpan Pinjam Kelompok Perempuan (SPP) Menggunakan Analisis Regresi Logistik Biner - Julinda Lestari; Media Rosha (UNIVERSITAS NEGERI PADANG, 2020)
Abstract–Simpan Pinjam Kelompok Perempuan (SPP) is one of the PNPM-MPd programs that lend capital to women's groups to improve household economy. The research is conducted to determine some factors that significantly influence the level of credit repayment in the SPP program in Padang Sago Subdistrict. We use a primary data obtained from interviews by using questionnaire. The questionnaire consisted of 12 questions were distributed to 50 respondents who made SPP credit payments in September 2019. The analysis method used in this study is binary regression with the rate of credit repayment as dependent variables. The regression parameters are estimated by using MLE technique, the model is constructed by using backward elimination method, and interpreted by using odds ratio. Based on the result we acquire two independent variables that are significantly affect to the rate of credit repayment i.e the loan amount and the short-term credit refund period. Keywords–Simpan Pinjam Kelompok Perempuan (SPP), credit repayment rate, binary logistic regression